The Eighteenth-Century Fortepiano Grand and Its Patrons : From Scarlatti to Beethoven - Badura-Skoda, Eva (Book collections on Project MUSE., 2017)
In the late 17th century, Italian musician and inventor Bartolomeo Cristofori developed a new musical instrument for his 'cembalo che fa il piano e forte', which allowed keyboard players flexible dynamic gradation. This innovation, which came to be known as the hammer-harpsichord or fortepiano grand, was slow to catch on in musical circles. However, as renowned piano historian Eva Badura-Skoda demonstrates, the instrument inspired new keyboard techniques and performance practices and was eagerly adopted by virtuosos of the age, including Scarlatti, J.S. Bach, Clementi, Haydn, Mozart, and Beethoven. Collecting a rich array of archival evidence, Badura-Skoda traces the construction and use of the fortepiano grand across the musical cultures of 18th-century Europe, providing a valuable resource for music historians, organologists, and performers.